Contribution of whole platelet aggregometry to the endovascular management of unruptured aneurysms: an institutional experience. (20th September 2016) - Aoun, S G; Welch, B G; Pride, L G; White, J; Novakovic, R; Hoes, K; Sarode, R
Abstract : Background: Stent-assisted coiling of intracranial aneurysms is an efficient alternative treatment to surgical clipping but requires prolonged antiplatelet therapy. Some patients are non-responsive to aspirin and/or clopidogrel. Objective: To analyze the implications of this assessment using the 'whole blood aggregometry (WBA) by impedance' technique. Materials and methods: The Southwestern Tertiary Aneurysm Registry was reviewed between 2002 and 2012 for patients with unruptured aneurysms treated with stent-assisted coiling. The study population was divided into patients who were tested preoperatively for platelet responsiveness to aspirin and clopidogrel ('tested' patients) and those who were not ('non-tested'). Where necessary, tested patients received additional doses of antiplatelet drugs to achieve adequate platelet inhibition. Endpoints included the incidence of non-responsiveness, the rates of thrombotic and hemorrhagic complications, and the rates of permanent morbidity and mortality. Results: A total of 266 patients fulfilled our selection criteria: 114 non-tested patients who underwent 121 procedures, and 152 tested patients who underwent 171 procedures. The two groups did not vary significantly in patient age, gender, and aneurysms location. Aspirin non-responsiveness was detected in 3 patients (1.75%) and clopidogrel non-responsiveness in 21 patients (12.3%). Non-tested patients had an 11.6% rate of thrombotic complications with a 4.1% permanent morbidity or mortality rate versus 2.3% and 0.6% in tested patients (p=0.0013). The incidence of hemorrhagic complications was similar between the two groups. Conclusions: Preoperative platelet inhibition testing using WBA can be useful to assess and correct antiaggregant non-responsiveness, and may reduce postoperative mortality and permanent morbidity.